DETEKSI Escherichia coli PATOGEN PADA PANGAN MENGGUNAKAN METODE KONVENSIONAL DAN METODE MULTIPLEX PCR - Evy Ratnasari Ekawati; Siti Nur Husnul Yusmiati; Fakhmi Rooslan Hamidi (Jurnal SainHealth, 2017)
Foodstuffs are a source of nutrition for humans and as well as a source of food for microorganisms. Microbes can contaminate food through water, dust, air, soil, processing tools (during production or preparation processes, as well as secretions from human and animal guts). Food can be toxic because it has been contaminated by pathogenic bacteria which can then grow and multiply during storage, so the bacteria are able to produce toxins that are harmful to humans. The aimed of this study was to detect the presence of Escherichia coli pathogen in food. This type of research is experimental laboratory using conventional method and multiplex PCR method. 8 positive samples of Escherichia coli ATCC 25922 by conventional method, consisting of 5 samples of tofu; 2 samples of ice syrup and 1 sample iced tea. All positive samples in EMB agar continued Escherichia coli pathogen detection using PCR multiplex method. From the PCR multiplex test, no samples were detected Escherichia coli pathogen